Fast calculation of the exponential function using tables - Vasilev, Eugene I.; Ionov Grigorii А.; Ionov Mikhail А. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2023)
In this paper, algorithms are described and compact software modules in the C language are presented for fast calculation of the exponential and logarithmic functions using tables for x86-64 architecture processors. The accuracy was evaluated and the performance was compared for some AMD and Intel processors. Generalization of the tabular approach has been implemented and tested for some trigonometric functions. On average, the proposed functions work 10 times faster than corresponding analogues from the standard mathematical library with prototypes in math.h.